2015
DOI: 10.5958/0975-6906.2015.00076.0
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of a MATE-type transporter gene ofArabidopsisand its orthologues in rice and chickpea under salt stress

Abstract: Salinity is one of the major abiotic stresses that adversely affect the crop growth and productivity. Salt responsive genes belonging to MATE efflux proteins reportedly play a significant role imparting salt tolerance to plants. In the present study, AT5G52050, a putative salt responsive gene from Arabidopsis thaliana encoding MATE efflux family protein which functions as an antiporter and its orthologues in rice (LOC_Os02g45380) and chickpea (LOC101489496) have been identified. The expression pattern of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It was observed that miRNA: car-miRNA015, Cat-miR159g-3p and Cat-miR172c.2 were targeting auxin response mutant (AXR4), Myb and Ethylene-responsive AP2 transcription factors respectively under stress along with several other interaction is shown in Table S9. We observed that several target genes of miRNAs were reported to play important role in salt stress like MATE efflux family protein (Nimmy et al 2015 ), Pentatricopeptide repeat-containing protein (Jiang et al 2015 , Chen et al 2018 ), Peroxidase (M'barek et al 2017 , Jin et al 2019 ), Ribonuclease (Zheng et al 2014 ), Squamosa promoter-binding-like protein (Hou et al 2018 , Wang et al 2019a ). This shows that identified lncRNAs in this study, play important role in indirect regulation of various salt stress genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that miRNA: car-miRNA015, Cat-miR159g-3p and Cat-miR172c.2 were targeting auxin response mutant (AXR4), Myb and Ethylene-responsive AP2 transcription factors respectively under stress along with several other interaction is shown in Table S9. We observed that several target genes of miRNAs were reported to play important role in salt stress like MATE efflux family protein (Nimmy et al 2015 ), Pentatricopeptide repeat-containing protein (Jiang et al 2015 , Chen et al 2018 ), Peroxidase (M'barek et al 2017 , Jin et al 2019 ), Ribonuclease (Zheng et al 2014 ), Squamosa promoter-binding-like protein (Hou et al 2018 , Wang et al 2019a ). This shows that identified lncRNAs in this study, play important role in indirect regulation of various salt stress genes.…”
Section: Resultsmentioning
confidence: 99%
“…Serval other eTMs like, MATE efflux family protein were also playing significant role under salt stress. MATE gene family mostly encodes transporter genes involved in various physiological process in plants (Nimmy et al 2015 ). Role and function of MATE efflux family under abiotic stress has been studied in various other crops like, rice (Du et al 2021 ), soybean (Liu et al 2016 ), tomato (Santos et al 2017 ), etc.…”
Section: Discussionmentioning
confidence: 99%
“…Pertinent to this property was a reported transcriptional profile of salt-stressed Arabidopsis roots that revealed the enrichment MATE transporters [ 97 ]. In addition, putative salt responsive MATE genes were identified in Arabidopsis, rice, and chickpea [ 98 ] whereas an Arabidopsis Golgi-localized MATE transporter was found to be induced by excessive iron and osmotic stress conditions [ 99 ]. In like manner, the up-regulation of a cyclic nucleotide gated Ca 2+ -permeable cation channel 5 gene in SS plants coincided with the proposed role for a similar channel in the conferral of salt tolerance to Arabidopsis [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…In higher plants, the land plants that have lignified tissues (the xylem) for conducting water and minerals throughout the plant, the MATE genes have been found to be involved in the transportation and transiting of xenobiotic and other small organic molecules, such as inositol hexakisphosphate, yokonolide B, p -chlorophenoxyisobutyric acid, toyocamycin and terfestatin ( Diener et al 2001 ; Tiwari et al 2014 ). Salt-responsive genes belonging to MATE efflux proteins have been reported to play a significant role in conferring salt tolerance in rice and chickpea ( Nimmy et al 2015 ). In addition, putative salt-responsive genes from the model plant Arabidopsis thaliana encoding the MATE efflux family have been identified and found to enhance salt tolerance ( Li et al 2002 ).…”
mentioning
confidence: 99%